KOHESI PARAGRAF DALAM BUKU TEKS EFL KELAS PENULISAN ESAI UNIVERSITAS NEGERI MAKASSAR - Muhmmad Nurul Multazam; Chairil Anwar Korompot; Geminastiti Sakkir (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aimed to provide descriptive accounts of the use of paragraph cohesion in the textbook in learning materials for an essay writing class at UNM Makassar. This research employed a qualitative approach with descriptive data exposure. Qualitative research is research that aims to describe research results. This research analyzes and reveals various qualitative information with a detailed description through cohesion in this textbook. The research design used is descriptive-analytical. This design is a research design that describes the research objectively. Researchers observe in-depth and conduct an in-depth analysis of the object of research. In the application of this research design, the first thing the researcher did was to collect data and references relevant to the object of research, sort and categorize the data found, process the data, and then present the data objectively following the results of interruptions to the object of research conducted. The findings showed. The data analysis presentation consists of (1) cohesion, which includes grammatical cohesion (reference, substitution, ellipsis, and conjunction), and lexical cohesion, which includes repetition, synonym, antonym, hyponym, and collocation. In this textbook, cohesion has an influential role in the learning activity. It is suggested that it is significant to In the preparation of textbooks, it is recommended to study the presentation of the learning material to make it easier for students to understand. To facilitate students' understanding of the material, each paragraph of the learning material in the textbooks of the essay writing course at UNM should pay more attention to cohesion. Keywords: Cohesion, Essay Writing, Qualitative Research.